2014
DOI: 10.1002/bjs.9627
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis according to histochemical analysis of liver metastases removed at liver resection

Abstract: Fibrotic capsule formation and localized cell infiltration of colorectal liver metastases by CD45RO(+) cells were related to prolonged patient survival. Based on these immunological criteria a cellular immune score was developed to stratify patients according to prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
72
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 31 publications
4
72
0
2
Order By: Relevance
“…To explain considerable outcome variations of patients staged in the same histological category, the immunological tumor microenvironment and its effect on patient outcome have been extensively investigated [2,3,4,5,6]. These studies of primary colorectal carcinomas have demonstrated beneficial survival effects of tumor infiltration by CD4 + Th1, CD8 + cytotoxic and CD45RO + memory T cells, whereas Th17 cell infiltration is associated with poor patient survival [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…To explain considerable outcome variations of patients staged in the same histological category, the immunological tumor microenvironment and its effect on patient outcome have been extensively investigated [2,3,4,5,6]. These studies of primary colorectal carcinomas have demonstrated beneficial survival effects of tumor infiltration by CD4 + Th1, CD8 + cytotoxic and CD45RO + memory T cells, whereas Th17 cell infiltration is associated with poor patient survival [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these new results, immune scores have been developed to prognosticate patient survival, which have been proposed as a new component for classification of primary colorectal carcinoma [10]. In addition to these scores, our group investigated colorectal liver metastases, which occur in 40-50% of patients with colorectal cancer and determine long-term survival, in order to elucidate their immune architecture [3]. In this study, we demonstrated that peritumoral infiltration of CD45RO + cells and a fibrotic capsule containing the liver metastases were independent prognosticators for prolonged survival of patients with colorectal liver metastases [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent data has supported that idea that growth patterns are probably relevant and may explain the link between margins and outcome. 4,5 The debate has certainly not been laid to rest.…”
mentioning
confidence: 99%